PENGARUH PIUTANG DAGANG DAN METODE PENCATATAN HUTANG PIUTANG TERHADAP KETERSEDIAAN MODAL PENJUALAN DALAM PERSPEKTI EKONOMI ISLAM (Studi Kasus Toko Bahan Pokok di Desa Tanjung Durian Kec. Buay Pemaca. Kab. OKUS) - Saputra, Tio Aryansah (El -Hekam, 2017)
At a shop located in the Village Tanjung Durian Kec. Buay Readers Kab. OKUS that sells various kinds of basic necessities of daily living, in this village there are 5 stores that sell various types of staples. The main problem lies in the accounts receivable given by the shopkeepers to the community in the village, how big is the influence, then do the shopkeepers practice the accounts payable according to Islamic principles, how is the availability of business capital of the shopkeepers in Nusamakmur village, and whether in the listing accounts payable in accordance with the principles of Islam that is recording correctly. The method used is quantitative method and qualitative method that is qualitative method is non statistical analysis which assist in research. The data obtained either in the form of numbers or in the form of tables and then interpreted well in accordance with the data obtained while the quantitative method is the analysis using statistical assistance to assist in research in calculating the figures to analyze the data obtained. Based on the results of research known methods of recording of the availability of business capital sales of staple goods Tanjung Durian Village Kec. Buay Readers Kab. OKUS does not fit the perspective of Islam this is shown from the financial statements of the data to five stores of staple goods two of which do not have complete financial statements of Marikun store and shop Lukman. Furthermore, there is a positive effect of trade receivables on the availability of venture capital sales, this is indicated from the analysis of accounts receivable turnover data from Jaaris shop 9.75 times or rounded up to (10 times) trade receivables turnover from Arifin shop 3.74 times rounded to become (4 times) the receivable turnover of shop of Muscah 16,92 rounded into (17 times). There is a positive negative effect of the turnover of accounts receivable to the capitalization of the sale of business is shown from the analysis of the financial statements of the store Jaemah by 4.32 times or 5 times, in turn, Arifin shop 3.55 times or 4 times and Musriah shop of 2, 31 times or 3 times in rotation.